Impact of incarceration on cardiovascular disease risk factors: a systematic review and meta-regression on weight and BMI change - Patrick Bodenmann; Constantin Bondolfi; Patrick Taffe; Aurélie Augsburger; Cécile Jaques; Mary Malebranche; Carole Clair (BMJ Open)
Objective Cardiovascular disease is an underappreciated issue in prison medicine. Recent studies have revealed a higher prevalence of cardiovascular disease risk factors (CVDRFs) among individuals in prison, but the impact of incarceration on CVDRFs over time is not well understood. This review aimed to assess available literature and quantify the relationship between incarceration and trends in major CVDRFs in high-income countries.Design Systematic review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Meta-regression on weight change and obesity.Data sources Medline, Embase, PubMed, Cochrane Central Wiley and Web of Science.Eligibility criteria for selecting studies Longitudinal studies reporting on the incidence of, or trends in any CVDRF among current or former people in prison over time, in high-income countries.Data extraction and synthesis Two authors independently screened articles for eligibility, extracted data and assessed quality using an adapted version of the Newcastle-Ottawa Scale. Trends in CVDRFs during and following incarceration were summarised and in those with sufficient data a meta-regression was performed.Results Twenty-six articles were identified. CVDRFs assessed included obesity, hypertension, diabetes, dyslipidaemia, tobacco use, physical inactivity and unhealthy diet. A meta-regression on change in weight during incarceration found a mean increase of 5.3 kg (95% CI 0.5 to 10.1) and change in body mass index of 1.8 kg/m2 (95% CI −0.9 to 4.6) at 2 years. Weight gain appeared most pronounced right after entering prison and then plateaued at 2 years. Concerning hypertension, the results were inconclusive, despite a trend towards rising blood pressure or prevalence of hypertension during incarceration, and an increased incidence of hypertension following incarceration. Results are contradictory or inconclusive for the other CVDRFs reviewed.Conclusion Possible explanations for the association between incarceration and weight include a sedentary lifestyle, unhealthy diet, forced smoking cessation, psychotropic medication use and high levels of stress. Incarceration may be an independent risk factor for cardiovascular disease.